Anomalous increase in specific heat of binary molten salt-based graphite nanofluids for thermal energy storage - Kim, Hyun Jung; Jo, Byeongnam (Applied Sciences (Switzerland), 2018)
An anomalous increase of the specific heat was experimentally observed in molten salt nanofluids using a differential scanning calorimeter. Binary carbonate molten salt mixtures were used as a base fluid, and the base salts were doped with graphite nanoparticles. Specific heat measurements of the nanofluids were performed to examine the effects of the composition of two salts consisting of the base fluid. In addition, the effect of the nanoparticle concentration was investigated as the concentration of the graphite nanoparticles was varied from 0.025 to 1.0 wt %. Moreover, the dispersion homogeneity of the nanoparticles was explored by increasing amount of surfactant in the synthesis process of the molten salt nanofluids. The results showed that the specific heat of the nanofluid was enhanced by more than 30% in the liquid phase and by more than 36% in the solid phase at a nanoparticle concentration of 1 wt %. It was also observed that the concentration and the dispersion homogeneity of nanoparticles favorably affected the specific heat enhancement of the molten salt nanofluids. The dispersion status of graphite nanoparticles into the salt mixtures was visualized via scanning electron microscopy. The experimental results were explained according to the nanoparticle-induced compressed liquid layer structure of the molten salts.
Keywords: Compressed liquid layer; Molten salt; Nanofluids; Nanoparticle dispersion; Specific heat; Thermal energy storage